Toward an Automated System for Nondestructive Estimation of Plant Biomass - Randall Kliman; Yuankai Huang; Ye Zhao; Yongsheng Chen (Plant Direct)
ABSTRACT Accurate and nondestructive estimation of plant biomass is crucial for optimizing plant productivity, but existing methods are often expensive and require complex experimental setups. To address this challenge, we developed an automated system for estimating plant root and shoot biomass over the plant's lifecycle in hydroponic systems. This system employs a robotic arm and turntable to capture 40 images at equidistant angles around a hydroponically grown lettuce plant. These images are then processed into silhouettes and used in voxel‐based volumetric 3D reconstruction to produce detailed 3D models. We utilize a space carving method along with a raytracing‐based optical correction technique to create high‐accuracy reconstructions. Analysis of these models demonstrates that our system accurately reconstructs the plant root structure and provides precise measurements of root volume, which can be calibrated to indicate biomass.